Fotobiomodulação da expressão e produção de mediadores inflamatórios por células pulpares irradiada com LED infravermelho - Montoro, Liege Aldrovandi [UNESP] (2013)
Aim: To investigate the effect of infrared light emitting diode (LED) irradiation (855nm), at different energy doses, on the production and expression of inflammatory mediators by cultured human dental pulp cells (HDPC). Methodology: HDPC were harvested from sound, near-exfoliation primary teeth. Cells were seeded (105 cells/well) using α-MEM supplemented with 10% FBS and after 24h, were exposed to LPS (10 μg/mL α-MEM) or TNF-α (25ng/mL α- MEM). Then, HDPC were submitted to a single irradiation with an infrared LED (855 nm) delivering different doses of energy: 0, 2, 4, 8, 15 or 30 J/cm2. Nonirradiated cells, with and without LPS/TNF-α, served as controls. Followed 24h, the cells stimulated with LPS were tested for nitric oxide (NO) quantification, cell viability (MTT assay), and reactive oxygen species (ROS) production (n=8 per group). Cells stimulated with TNF-α were analyzed regarding cytokine production and expression using antibody array and q-PCR (n=5 per group). Data were submitted to Kruskal-Wallis and Mann-Whitney tests (α=0.05). Results: LPSinduced stress resulted in significant increase in NO production by HDPC without causing any damage to cell respiratory metabolism. Irrespective of the energy dose delivered, NO production was significantly reduced when LPS-stressed cells were irradiated. The best effect was observed when 15 J/cm2 were delivered to cells. Infrared LED irradiation also promoted decrease in ROS production, while HDPC metabolism was not significantly affected. The most produced cytokines in cells stimulated with TNF-α were: GROα, IL-6, IL-8, TNF α, MCP-1 and E1 Serpin. qPCR analysis showed a decrease in expression of IL- 1 β when the cells were irradiated with the dose of 4 J/cm2. Conclusion: The oxidative stress of HDPC can be biomodulated by a single irradiation of an infrared LED. Regarding the expression of inflammatory cytokines, the delivery of 4 J/cm2 was...